Nanocatalysts: Achieving Efficient Alkaline Hydrogen Evolution Reaction over a Ni5P4 Catalyst Incorporating Single‐Atomic Ru Sites (Adv. Mater. 11/2020). Issue 11 (17th March 2020) - He, Qun; Tian, Dong; Jiang, Hongliang; Cao, Dengfeng; Wei, Shiqiang; Liu, Daobin; Song, Pin; Lin, Yue; Song, Li
Abstract : Hydrogen production from electrochemical water splitting is very promising but still challenging. In article number 1906972, Li Song and co‐workers develop nickel phosphide nanocatalysts incorporated with single‐atomic noble metal for highly efficient alkaline water electrolysis. The doped metallic sites can cause localized structure polarization, largely promoting the hydrogen evolution from phosphide catalysts.